2001
DOI: 10.1177/00220345010800111601
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Modeling of Jaw-closing Movement during Food Breakage

Abstract: It has been demonstrated that the vertical jaw movement trajectories during gum-chewing can be explained by jerk-cost minimization. However, it is uncertain whether the masticatory jaw movement in space can be predicted by the minimum-jerk model. The aims of the present study were to develop minimum-jerk models that would explain 3D masticatory jaw movements with different hardnesses of foods, and to evaluate if the models can predict the movements accurately. The 3D masticatory jaw movement during food breaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…The factual masticatory jaw-movement trajectories were found to be highly correlated with the model-based trajectories, 13,14 which were computed on the basis of a modeling technique 10 reported previously. In addition, jerkcost has been shown to be highly sensitive and proportional to the degree of occlusal interferences that have been experimentally induced by inserting acrylic fillings with varying vertical dimensions.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…The factual masticatory jaw-movement trajectories were found to be highly correlated with the model-based trajectories, 13,14 which were computed on the basis of a modeling technique 10 reported previously. In addition, jerkcost has been shown to be highly sensitive and proportional to the degree of occlusal interferences that have been experimentally induced by inserting acrylic fillings with varying vertical dimensions.…”
mentioning
confidence: 60%
“…A detailed description of the mathematical data processing methods has been reported previously. 13,14 The minimum-jerk model 10,20,21 was applied to the factual jaw displacement trajectory data of the jaw-closing phase for each chewing cycle. The accuracy of the model prediction was measured by using Spearman's correlation coefficient (r) between the actual and predicted velocity profiles.…”
Section: Data Recording and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A normalization technique was applied to the jerk-cost data analysis. The normalization technique generates a measure of jerk-cost which is independent of duration and amplitude of the movement (normalized jerk-cost, NJC 22,27 ). The jerk-cost was analyzed at the jaw closing phase because the high NJC during jaw closing in chewing closely relates to a skewed velocity profile with a prolonged period of deceleration.…”
Section: Discussionmentioning
confidence: 99%
“…The jerk-cost has demonstrated its usefulness as a parameter in the evaluation of masticatory movement. 21,22 One jerk analysis of jaw movement demonstrated that artificial occlusal interferences significantly decreased the smoothness of masticatory jaw movement during gum chewing. 23 Another study used jerk-cost analysis to effectively detect a significant increase of the smoothness of jaw movement after correction of the malocclusions.…”
Section: Introductionmentioning
confidence: 99%